Modeling Life Expectation of Population in Sumatra Island Using Durbin Spatial Model Analysis: Modeling Life Expectation of Population in Sumatra Island Using Durbin Spatial Model Analysis - Aulia, Sartika Mega; Sirait, Haposan (Communication In Research And Publications, 2023)
Life expectancy is an indicator in measuring government performance in improving the level of health and well-being of the population of a region. While life expectancy on Sumatra Island has variable values, the quality of public health is less uniform. These variations can be caused by several factors such as education, health services, and economic conditions. Therefore, the government needs to provide further treatment on Sumatra Island by identifying factors that affect life expectancy. The study used a Spatial Durbin Model with Queen Contiguity and Rook Contiguity 154 districts/cities on the island of Sumatra. The variables used in the study were data on life expectancy, average school age, the percentage of many infants who received complete immunization, the percent of households having access to decent drinking water, the proportion of the poor population, the regional gross domestic product in 2021. The results of the study showed that the best model was the model that used the Queen Contiguity weighing matrix because it had a smaller AIC value of 365.22. Factors influencing the life expectancy of the population of Sumatra Island in 2021 using the durbin spatial model with the Queen weigher are the average age of school, the percentage of the poor population, and the regional gross domestic product.